The Battle Against Colorado Potato Beetle in the Soviet Lithuania: Viewpoints, Structures and Practices - Kereišiūtė, Agnė (Vilnius University Open Series, 2025)
The Colorado potato beetle, which spread across Europe after World War One and reached the Soviet Lithuania in the second half of the 1950s, eventually took over not only the potato fields but also the imagination of potato growers. The myths surrounding this pest have received some attention in foreign historiography, but, in Lithuania, the issue has been virtually untouched, although associative images such as collective searches, bottles of kerosene, and puzzling theories of how the beetle came to be, although faded, have survived to this day. The study seeks to reveal three key moments: the evolution of the discourse, the mechanisms (structures and principles of containment) that were supposed to realise the superiority of the planned struggle declared by the Soviets, as well as the practical, actual expression of the struggle.